Perlindungan Hukum Terhadap Korban Perdagangan Orang Di Negara Indonesia Dan Negara Thailand - Siti Nurjanah; Bernice Bernice (Journal of Judicial Review, 2015)
Human trafficking is the trade of humans, most commonly for the purpose of sexual slavery, forced labor or commercial sexual exploitation for the trafficker or others. Human trafficking is a crime against the person because of the violation of the victim's rights of movement through coercion and because of their commercial exploitation. Although human trafficking can occur at local levels, it has transnational implications, as recognized by the United Nations in the Protocol to Prevent, Suppress and Punish Trafficking in Persons, especially Women and Children(also referred to as the Trafficking Protocol or the Palermo Protocol.Methodology used in this research is the normative legal research -based comparative law. The data used in this study is a secondary data obtained from literature (library research). Once all the data is collected, then processed and analyzed to find the legal issues that are the object of study and conclude , then described descriptively.The results of this study indicate that Indonesia and Thailand respect the rights of victims of human trafficking by ratifying the Protocol to Prevent, Suppress, and Punish Trafficking in Persons, Especially Women and Children supplementing the United Convention against Transnational Organized Crime. Indonesia was placed in Tier 2 while Thailand does not fully comply the minimum standards in providing protection to victims and are placed in Tier 3 in 2014.